Respuesta :

Answer:a = - 2

b = - 3

c = 3

Step-by-step explanation:

a + 5b - c = - 20 - - - - - - - - - 1

4a - 5b + 4c = 19 - - - - - - - - - 2

-a - 5b - 5c = 2 - - - - - - - - - - - 3

Adding equation 1 and equation 2, it becomes

- 6c = - 18

c = - 18/ - 6 = 3

Multiplying equation 2 by 1 and equation 3 by 4, it becomes

4a - 5b + 4c = 19

-4a - 20b - 20c = 8

Adding both equations, it becomes

- 25b - 16c = 27

- 25b = 27 + 16c = 27 + 16 × 3

- 25b = 75

b = 75/- 25 = - 3

Substituting b = - 3 and c = 3 into equation 1, it becomes

a + 5 × - 3 - 3 = - 20

a - 15 - 3 = - 20

a - 18 = - 20

a = - 20 + 18 = - 2